Optimal profit sharing contract and principal-agent value in islamic bank - Sapuan N.M.; Sanusi N.A.; Ismail A.G.; Wibowo A. (American Scientific Publishers, 2023)
The principal-agent problems in the Islamic banking system, especially in profit sharing (mudarabah) contract are severe without effective dissemination of information between the contracting parties. In profit sharing (mudarabah) contract, the realized profit is influenced by information. In this study, we provide suggestion in mitigating the principal-agent problem and increasing the returns of the contracting parties through the shuratic process (mutual consultation). Hence, the objective of this study is to empirically examine the optimal condition of profit sharing ratio (PSR) and shuratic process for profit sharing contract based on a simulation technique for Islamic banking in Malaysia. The results showed that the trend of shuratic process has a positive relationship with the trend of Islamic banks net profit. Additionally, the results also indicated that the Islamic banks net profit has a positive relationship to the Islamic banks profit sharing ratio (PSR) for profit sharing (mudarabah) financing and securities investment activities. On the other hand, there is a negative relationship between the Islamic banks PSR from return on financial and securities investment activities and the entrepreneurs PSR. The results also revealed that there is a positive relationship between the PSR for investment saving accounts and the Islamic banks net profit. However, depositors will earn less return from their deposits. 2015 American Scientific Publishers. All rights reserved.